Intellectual Property as Complex Innovation Projects Component - Bukhkalo, Svitlana; Denysovets, Iryna; Galagan, Natalia; Dumenko, Hanna (International Journal of Engineering and Technology, 2018)
The materials presented the possibilities development of intellectual property complex innovation projects modern highly effective science-based problems of improving the use of wastes of different industries on a complex enterprise that can provide all its energy needs alone. Some features of the possibilities of solving evidence-based problems of development of mechanisms for identifying synergistic processes, their scientific justification improving the use of wastes of different industries on a complex enterprise. The problem of wastes utilization and recycling is present as complex synergetic processes research and analysis of energy- and resource saving processes for treatment of polymer wastes of various origin. The research focused on the study of issues such as the development of models of waste-modifying polymer. The investigation are focused in researching such problems as selection of scientific based methods of wastes to be utilized or recycled; the development of appropriated process flow sheets and choice of modifications additives and equipment for polymers waste recycling. The choice of appropriate plants with selected energy resources is very important for projects realization.Â Â Â